Enhanced Thermal Performance Analysis Of Engine Cooling Fins With Varying Geometries And Materials (International Journal of Environmental Sciences, 2025)
The engine cylinder is one of the most heat-intensive components in internal combustion engines, often operating under extreme thermal conditions. To regulate the temperature and maintain performance, air-cooling methods are commonly adopted, where fins are integrated onto the cylinder's exterior to improve heat transfer by increasing surface area. This research investigates how modifications in fin geometry and material composition influence thermal performance. The study explores circular, wavy, and longitudinal rectangular fin configurations, using materials such as cast iron, aluminum 6061, and aluminum 2014. Using ANSYS Space Claim, 3D models were designed, and thermal simulations were carried out in ANSYS to evaluate temperature profiles and heat flux. The findings reveal that wavy fins with AL2014 material provide superior cooling capabilities compared to other shapes and materials due to better heat dissipation efficiency.